BODY IMAGE, PERILAKU MAKAN DAN STATUS GIZI REMAJA: Body Image, Eating Behavior and Nutritional Status in Adolescents - Ni Luh Agustini Purnama (LPPM STIKES Pemkab Jombang, 2021)
Introduction: Adolescents need balanced nutrition to increase physical growth and development very rapidly. In Indonesia, the nutritional problems in adolescents are complex, namely obesity, malnutrition, and micronutrient deficiencies such as anemia. Adolescent nutritional status is influenced by various factors such as eating behavior and body image. Objective: This study aims to identify the relationship between eating behavior, body image, and nutritional status of adolescents. Method: The research design used cross-sectional. Respondents were 62 teenagers at SMAK Karitas 3 Surabaya who met the inclusion criteria and was taken using a simple random sampling technique. Eating behavior was assessed using the Eating Behavior Patterns Questionnaire. Body image is assessed by questionnaire and adolescent nutritional status is based on body mass index. Results: The study showed that 56.5% of adolescents had a positive body image, 93.5% of adolescents with healthy eating behavior and 35.5% of nutritional status based on body mass index were in the normal category. Spearman correlation test showed that there was a significant relationship between body image and adolescent nutritional status, with a negative correlation (p = 0.0001, r = -0.447). There was no relationship between eating behavior and nutritional status of adolescents (p=0.711). Conclusion: Body image is related to nutritional status, where the increase in nutritional status will be followed by a decrease in body image. Although the eating behavior of adolescents is healthy, they still experience nutritional status disorders, namely overweight and obesity, so further research needs to be done regarding other factors such as a physical activity that can affect the nutritional status of adolescents